Sains Indonesia: Pengembangan LKPD Berbasis STEM dengan Pendekatan Problem Based Learning terhadap Keterampilan Proses Sains dan Kemampuan Berpikir Kritis pada Pembelajaran IPA - Budiyatno; Suseno, Nyoto; Aththibby, Arif Rahman (PendIPA Journal of Science Education, 2024)
This research aimed to develop Student Worksheets based on STEM using a Problem-Based Learning (PBL) approach to enhance students' science process skills and critical thinking abilities in science learning at junior high school SMP Abadi Perkasa. The development model used is ADDIE, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Product validation was conducted by experts in language, content, and media, demonstrating good reliability with a Cronbach’s Alpha value of ≥ 0.7. The implementation of the Student Worksheets was carried out with Grade IX students at SMP Abadi Perkasa, and the trials showed a significant improvement in students' skills. The N-gain analysis results reached an average of 0.56, categorized as "moderate," indicating an improvement in students' science process skills and critical thinking abilities. Student response questionnaire data indicated the effectiveness of the Student Worksheets, with an average score of 3.56 and an effectiveness percentage of 89.1%, falling into the "effective" category. The findings of this study suggest that the application of STEM-based Student Worksheets with a PBL approach positively impacts science learning, particularly in the topic of dynamic electricity, by enhancing students' science process skills and critical thinking abilities through a more contextual and interactive learning approach.